การพัฒนาการควบคุมสำหรับหุ่นยนต์โคบอทปรับขนาด - จอมมุทธา จำปาเหลือง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Cobots (Collaborative Robot) are passive devices that designed to work directly with an operator. Cobot technology can be applied to several areas ranging from haptic interface, human-robot interaction, ergonomic material handling, assembly operations, medical applications, and assistive devices. This paper presents a resizable Cobot that has a three dimensional planar workspace. The Cobot can change its size so that it can maneuver effectively in a tight space. Current Cobot controls are based on feed forward and feedback controls. The feed forward command is mainly calculated from Cobot kinematics, and the feedback control is implemented within its configuration space. However, previous feedback control is insufficient to compensate the error that occurs when the resizable Cobot moves along a complex reference path. In this work, we improve the control with additional feedback in the wheel space. Furthermore, in this research, the new 4-dimensional control (combination of configuration space and the expansion space) is presented. The experiment with wheel space feedback and 4-dimensional path planning provide satisfactory results with low tracking error. The resizable Cobot can follow along command paths and preserve its expansion according to the reference.